2009
DOI: 10.1073/pnas.0809671106
|View full text |Cite
|
Sign up to set email alerts
|

Impact of sideways and bottom-up control factors on bacterial community succession over a tidal cycle

Abstract: In aquatic systems, bacterial community succession is a function of top-down and bottom-up factors, but little information exists on ''sideways'' controls, such as bacterial predation by Bdellovibriolike organisms (BLOs), which likely impacts nutrient cycling within the microbial loop and eventual export to higher trophic groups. Here we report transient response of estuarine microbiota and BLO spp. to tidal-associated dissolved organic matter supply in a riverdominated estuary, Apalachicola Bay, Florida. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
75
0
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 43 publications
6
75
0
9
Order By: Relevance
“…Although the significance of Bacteriovorax community structure and diversity is only beginning to be recognized (Chauhan et al, 2009), in general, biodiversity has been reported to be an important factor in ecosystem function and responses to environmental changes (Bell et al, 2005;Fuhrman, 2009). Regarding services of BALO populations in the environment, diversity is likely an important factor, especially relative to their potential function in controlling and shaping bacterial communities through selective mortality, which may be dependent upon the specific predator OTUs present.…”
Section: Prey Bacteria Select Predators H Chen Et Almentioning
confidence: 99%
“…Although the significance of Bacteriovorax community structure and diversity is only beginning to be recognized (Chauhan et al, 2009), in general, biodiversity has been reported to be an important factor in ecosystem function and responses to environmental changes (Bell et al, 2005;Fuhrman, 2009). Regarding services of BALO populations in the environment, diversity is likely an important factor, especially relative to their potential function in controlling and shaping bacterial communities through selective mortality, which may be dependent upon the specific predator OTUs present.…”
Section: Prey Bacteria Select Predators H Chen Et Almentioning
confidence: 99%
“…BALOs are well distributed in nature, being found in both terrestrial and aquatic ecosystems and possibly in animal (including human) intestines (11,16,17). Because obligate predators cannot replicate in the absence of adequate prey, the structure of BALO populations is under environmental selection (6,7,18), whereas natural selection and arms race may shape predator-prey interactions (19,20). Indeed, BALO isolates possess different prey spectra that are adapted to the prey available in their surroundings (18,21,22).…”
mentioning
confidence: 99%
“…However, predation between bacteria, the most abundant cellular living entities on Earth, is poorly understood. The known diversity of predatory bacteria is low (4), and few studies have addressed predation dynamics in natural or man-made environments (5)(6)(7). An important aspect of predatory interactions is prey choice.…”
mentioning
confidence: 99%
“…The DON absorbed by prokaryotes is believed to be transported indirectly to aquatic animals at higher trophic levels via the food chain for use as a nutrient source. This pathway is known as a 'bottom-up cascade', in which DON increases prokaryotic abundance, the abundant prokaryotes are subsequently consumed by protozoa, which are then consumed by zooplankton and so on [5]. In other words, current food-web theory assumes that nutrients flow from DON to aquatic animals via long pathways involving multiple eukaryotic species as intermediary nutrient transporters [6].…”
Section: Introductionmentioning
confidence: 99%